Agents and livability: constructing the underlying premises of local sustainability - Abdul Samad Hadi; Abdul Hadi Harman Shah; Shaharudin Idrus; Ahmad Fariz Mohamed; Ruslan Rainis; Narimah Samat (Environmental Management Society, Malaysia, 2009)
The deconstruction of development through the processes of local agency, looking at how local actors, situations and path dependence result in the patterns of physical development of a region, provides a different perspective to the urbanization process in Malaysia. The more common approach is by looking at how macro and meso changes impact upon the local scenes. The alternative complexity analysis approach used in this article allows for a better understanding on how the local situation impacts upon the macro and meso urbanization observed through land use and economic activity changes. Using the Bernam-Linggi basin as a living laboratory of urbanization, this article presents the concepts used to structure a study on local urbanization and the resulting sustainability conditions that result from such changes. The study also emphasizes multidisciplinarity and the effects of uncertainties in analysing the socio-spatial dynamics of the region